Effect of turmeric (Curcuma longa L.) on blood glucose control in patients with diabetes mellitus - Ranti Ningsih Sumarni; Atik Aryani; Fajar Alam Putra; Laras Adi Rantika Sari (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Diabetes mellitus (DM) cases remain a global concern. DM is often referred to as the "silent killer" because its symptoms are often not noticeable in the early stages. DM can cause serious complications, such as kidney damage and even amputation. This is a serious public health issue. DM requires long-term treatment because it is a chronic disease that will be suffered with for life, where optimal blood sugar level management is the main focus of its treatment. Long-term medical treatment for DM often causes side effects and places a significant economic burden on patients. A natural, safe, and affordable supportive therapy approach is essential as part of comprehensive DM management. One plant with potential as a supportive therapy is turmeric leaf (Curcuma longa). Purpose: To determine the effectiveness of turmeric leaf decoction (curcuma longa) as a supportive therapy in lowering blood sugar levels in patients with diabetes mellitus. Method: This study was quasi-experimental and used a one-group pre-test-post-test design with control. The sample consisted of 60 DM patients (30 patients in the control group and 30 patients in the intervention group) who were treated at the Trucuk Klaten Community Health Center. The sampling technique used was purposive sampling. Blood sugar levels in the sample were measured using a glucometer. The data results were measured using the Mann-Whitney test. Results: Turmeric leaf decoction affected lowering blood sugar levels in diabetic patients with a p-value = 0.001 (p<0.005).  Conclusion: This non-pharmacological therapy using turmeric leaf decoction can be used as a supportive therapy for diabetic patients because it contains bioactive compounds such as flavonoids, tannins, and saponins, which are believed to have the potential to help lower blood glucose levels.